Effect Of Quality Of Work Life On Work Stress, Mental Health, Organizational Citizenship Behavior, And Performance Of Inpatient Nurses In Muhammadiyah HospitalType D East Java - Sunaryadi; Budiyanto; Suhermin (Publisher Cv. Inara, 2021)
Research related to the relationship between QWL, work stress, mental health, OCB and nurse performance in the type D Muhammadiyah Hospital network in East Java. Based on the problems, phenomena that occur in hospitals today as well as literature studies, researchers examine and analyze the effect of the QWL variable on the performance of inpatient nurses in the type D Muhammadiyah Hospital network in East Java. The population of this study were all nurses with the status of nurses in Muhammadiyah hospital type D, East Java. The sampling technique was saturated sample. The sample of this study was the entire population of nurses with the status of nurses who served in the inpatient room. This study was analyzed using the Partial Least Square method. The results of this study are QWL has a significant and positive effect on the performance of inpatient nurses in the Muhammadiyah type D hospital network in East Java; QWL has a significant and negative effect on the work stress of inpatient nurses in the Muhammadiyah type D hospital network in East Java; QWL has a significant and positive effect on the mental health of inpatient nurses in the Muhammadiyah type D hospital network in East Java; Job stress has a significant and negative effect on OCB of inpatient nurses in the Muhammadiyah type D hospital network, East Java; Mental Health has a significant and positive effect on OCB of inpatient nurses in Muhammadiyah type D Hospital, East Java; QWL has a significant and positive effect on OCB of inpatient nurses in the Muhammadiyah type D hospital network in East Java; OCB has a significant and positive effect on the performance of inpatient nurses in the Muhammadiyah type D hospital network in East Java.